Preparation method of MOF / graphene oxide / conducting polymer ternary composite material

By synthesizing MOF on the surface of graphene oxide nanosheets in situ and introducing conductive polymers, MOF/graphene oxide/conductive polymer ternary composites are constructed, and the problems of slow ion/electron transfer and structural instability in the MOF/conductive polymer binary composites are solved, and high specific capacitance and good cycling stability are achieved.

CN119889943APending Publication Date: 2025-04-25SHANDONG UNIV OF SCI & TECH
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411871292.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

MOF/conductive polymer binary composites have problems in supercapacitors with slow ion/electron transfer kinetics and unstable conjugated structure of conductive polymers.

Method used

By synthesizing MOF in situ on the surface of two-dimensional graphene oxide nanosheets, MOF/graphene oxide binary composite materials are constructed, and conductive polymer monomers and organic dopants are introduced on the basis of it to construct MOF/graphene oxide/conductive polymer ternary composite materials.

Benefits of technology

The ternary composite material significantly improves the ion/electron transfer rate and cyclic stability through the tight binding of MOF with graphene oxide and the orderly growth of conductive polymers, showing a high specific capacitance and long cycle life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119889943A_ABST
    Figure CN119889943A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an MOF / graphene oxide / conducting polymer ternary composite material, which comprises the following steps of: firstly, growing MOF particles on a graphene oxide sheet in situ by utilizing multiple hydrogen bonds and pi-pi interaction of rich oxygen-containing functional groups on the surface of graphene oxide and an MOF ligand; a functional dopant is utilized to modify an MOF / graphene oxide binary composite material, a conductive polymer monomer is introduced on the basis, and a chemical oxidation polymerization method is utilized to prepare the MOF / graphene oxide / conductive polymer ternary composite material. The method is simple in preparation process and convenient to operate, the prepared ternary composite material constructs a three-dimensional porous structure with lamellar lap joint, and in-situ growth of the MOF and the conductive polymer on the surface of the graphene oxide nanosheet is beneficial to improvement of energy density and cycling stability of the composite material serving as a supercapacitor electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new materials for supercapacitors, and specifically relates to a method for preparing a MOF / graphene oxide / conductive polymer ternary composite material. Background Art

[0002] In recent years, due to the depletion of conventional energy and its damage to the environment, the development of clean and renewable energy such as solar energy and wind energy has become increasingly important. However, the utilization of this green energy is limited by intermittency and instability. Researching various energy storage and conversion devices, such as supercapacitors, secondary batteries, and fuel cells, is an effective strategy to solve this problem. Among them, supercapacitors have a larger energy density than traditional capacitors and a higher power density than secondary batteries. At the same time, they have significant advantages such as long cycle life and environmental friendliness. Therefore, they have become an ideal power supply device for the new generation of intelligent, miniaturized, and wearable electronic devices. The performance of supercapacitors is mainly determined by the electrode material. Therefore, in supercapacitor technology, the development of new electrode materials is of great significance.

[0003] The doping-undoping characteristics of conductive polymers give them good redox activity, and they can obtain high Faraday pseudocapacitance as supercapacitor electrode materials, but they still have the following disadvantages: first, the actual specific capacitance is lower than the theoretical value; second, during long-term charge and discharge, conductive polymers usually have poor cycle stability. The main reason is the volume effect caused by doping-undoping during the charging and discharging process, which leads to the collapse of the polymer chain structure. Metal-organic framework compounds (MOFs) are porous materials with three-dimensional topological structures formed by self-assembly of metal ions (usually transition metal ions) and organic ligands. They have abundant active sites and huge specific surface area, but their poor conductivity limits their supercapacitor properties. Therefore, researchers combined conductive polymers with MOFs to synergistically improve the conductivity of MOFs and the cycle stability of conductive polymers. For example, Dubey et al. [DUBEY P, SHRIVASTAV V, SUNDRIYAL S, et al. Sustainable Nanoporous Metal–Organic Framework / Conducting Polymer Composites for Supercapacitor Applications [J]. ACS Applied Nano Materials, 2024, 7 (16): 18554-18565.] synthesized high-performance Cu-MOF / polypyrrole nanocomposites by in-situ hydrothermal technology. The introduction of polypyrrole not only improves the conductivity of the nanocomposite, but also constructs a MOF-polypyrrole-MOF transmission channel, which is conducive to the rapid transmission of ions. The electrochemical performance of the composite material is improved, showing a high specific capacitance (132.5 F / g) and excellent cycle stability (capacitance retention rate of up to 93.4% after 10,000 charge and discharge cycles). Yue et al. [YUE T, HOU R, LIU X, et al. Hybrid architecture of a porous polypyrrole scaffold loaded with metal–organic frameworks for flexible solid-state supercapacitors [J]. ACS Applied Energy Materials, 2020, 3 (12): 11920-11928.] used Cu-MOF and porous polypyrrole as electrode materials for flexible supercapacitors. The three-dimensional porous polypyrrole provides a conductive skeleton for MOF, and the Cu-MOF crystals are evenly distributed in the pores. The mass specific capacitance of the composite material can reach 343F / g. The composite material has stable cycling performance, and the capacitance retention rate exceeds 85% in 5000 charge and discharge cycles. Summary of the invention

[0004] In order to effectively solve the problems of slow ion / electron transfer kinetics and unstable conjugated structure of conductive polymer that still exist when MOF / conductive polymer binary composite materials are used as electrode materials. The present invention synthesizes MOF in situ on the surface of two-dimensional graphene oxide nanosheets to construct a MOF / graphene oxide binary composite material. On this basis, conductive polymer monomers and organic dopants are further introduced to in situ construct a MOF / graphene oxide / conductive polymer ternary composite material. On the one hand, MOF is anchored on the surface of graphene oxide sheets, which can effectively solve the stacking problem of graphene oxide sheets, and graphene oxide can provide a good conductive path for MOF with poor conductivity. On the other hand, under the induction of functional dopants, conductive polymer monomers can be orderly grown on the surface of MOF / graphene oxide composite materials through multiple hydrogen bonds and conjugated effects.

[0005] In order to achieve the above-mentioned object of the invention, the technical solution adopted by the present invention is as follows.

[0006] A method for preparing a MOF / graphene oxide / conductive polymer ternary composite material comprises the following steps:

[0007] (1) M(NO 3 ) 2 The solution and the graphene oxide solution are fully mixed, and then the 2-methylimidazole solution is added dropwise to the mixed solution, and the reaction is carried out at room temperature for 8-24 hours.

[0008] The M(NO 3 ) 2 Co(NO 3 ) 2 ,Ni(NO 3 ) 2 、Zn(NO 3 ) 2 One of the following; the M(NO 3 ) 2 The molar concentration of is 2 mM; the molar concentration of 2-methylimidazole is 2-20 mM, the concentration of graphene oxide is 0.06-0.24 mg / mL; and the reaction time is 8-24 h.

[0009] (2) The solution obtained in step (1) is centrifuged, washed, and freeze-dried to obtain MOF / graphene oxide binary composite material powder.

[0010] The centrifugal speed is 5000-10000rpm, the centrifugal time is 5-20min, and the freeze-drying time is 12-36h.

[0011] (3) dispersing the powdered MOF / graphene oxide binary composite material obtained in step (2) in an aqueous solution of a dopant, stirring and ultrasonically dispersing to obtain a dispersion I for later use.

[0012] The dopant is one of phosphomolybdic acid, phosphotungstic acid, ammonium molybdate, and silicomolybdic acid; the concentration of the MOF / graphene oxide solution is 1-2 mg / mL, the molar concentration of the dopant is 3-18 mM, the stirring time is 1-2 h, and the ultrasonic dispersion time is 10-30 min.

[0013] (4) Inject the conductive polymer monomer into the dispersion I obtained in step (3), stir and disperse by ultrasonic to obtain dispersion II for later use.

[0014] The conductive polymer monomer is one of aniline, pyrrole and 3,4-ethylenedioxythiophene, and its concentration is 2 mg / mL; the stirring time is 5-20 minutes, and the ultrasonic dispersion time is 10-30 minutes.

[0015] (5) adding an aqueous ammonium persulfate solution dropwise to the dispersion II obtained in step (4) to react, and finally washing and drying to obtain a MOF / graphene oxide / conductive polymer ternary composite material.

[0016] The molar ratio of the ammonium persulfate to the conductive polymer monomer is 2:1-1:2, and the reaction is carried out at room temperature for 12 hours.

[0017] The beneficial effects of the present invention are as follows:

[0018] 1. In the ternary composite material constructed by the present invention, two-dimensional graphene oxide is used as the carrier of MOF, which realizes the close combination of MOF and graphene oxide, and effectively solves the problem of easy accumulation of two-dimensional graphene oxide sheets and poor conductivity of MOF; on the other hand, the in-situ introduction of functional dopants can realize the secondary in-situ growth of conductive polymers in the two-dimensional structure MOF / graphene oxide composite sheets; the synergistic effect of the three can effectively improve the ion / electron transmission rate of the composite electrode material, and at the same time obtain a stable doping structure, which has not been reported in domestic and foreign literature.

[0019] 2. The MOF / graphene oxide / conductive polymer ternary composite material prepared by the method of the present invention exhibits high specific capacitance and cycle stability, and has broad application prospects as a supercapacitor electrode material.

[0020] 3. The method of the present invention adopts an in-situ synthesis method, which has simple equipment, easy operation, and is easy to expand into large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1This is a SEM photograph of the MOF / graphene oxide binary composite material prepared in Example 1 of the present invention.

[0022] Figure 2 This is a SEM photograph of the MOF / graphene oxide / conductive polymer ternary composite material prepared in Example 1 of the present invention.

[0023] Figure 3 This is a photo of a supercapacitor device assembled as Example 1 of the present invention lighting up an LED.

[0024] Figure 4 The MOF / graphene oxide / conductive polymer ternary composite material prepared in Example 1 of the present invention, wherein (a) CV curves at different scan rates; (b) GCD curves at different current densities; (c) EIS curves; and (d) cycle stability (current density is 10 A / g). DETAILED DESCRIPTION

[0025] The present invention is further described in detail below through specific examples.

[0026] Example 1

[0027] A method for preparing a MOF / graphene oxide / conductive polymer ternary composite material, the preparation steps are as follows:

[0028] (1) 0.1 mmol (0.0189 g) of Zn(NO 3 ) 2 , 3.0 mg of graphene oxide and 0.8 mmol (0.0657 g) of 2-methylimidazole were dissolved in 10, 30, and 10 mL of methanol solution, respectively. 3 ) 2 The mixture was fully mixed with the methanol solution of graphene oxide, and then the methanol solution of 2-methylimidazole was added dropwise to the mixed solution, and the mixture was reacted at room temperature for 8 hours;

[0029] (2) The reaction solution obtained in step (1) was centrifuged at 5000 rpm for 20 min to collect the product, and then washed with methanol three times. The composite material was then dissolved in deionized water and freeze-dried for 12 h, and finally the prepared composite material was ground to obtain a dry MOF / graphene oxide binary composite material;

[0030] (3) 0.06 mmol (0.1106 g) of phosphomolybdic acid was dissolved in 15 mL of deionized water, and then 20 mg of the MOF / graphene oxide binary composite material obtained in step (2) was added to the phosphomolybdic acid solution, stirred for 1 h, and ultrasonically dispersed for 10 min to obtain a uniformly mixed dispersion I for standby use;

[0031] (4) injecting 0.6 mmol (40 mg) of pyrrole monomer into the dispersion I obtained in step (3), stirring for 5 min, and ultrasonically dispersing for 30 min to obtain a uniformly mixed dispersion II for later use;

[0032] (5) 0.6 mmol (0.1369 g) of ammonium persulfate was dissolved in 5 mL of deionized water, and then added dropwise to the dispersion II obtained in step (4), reacted at room temperature for 12 h, then filtered, repeatedly washed with deionized water, and finally dried to obtain a MOF / graphene oxide / conductive polymer ternary composite material.

[0033] Figure 1 The SEM photo of the MOF / graphene oxide binary composite material shows that the MOF particles grow evenly on the graphene oxide nanosheets, which effectively solves the problem of easy accumulation of graphene oxide sheets and poor conductivity of MOF; Figure 2 The SEM image of the MOF / graphene oxide / conductive polymer ternary composite material shows that polypyrrole nanoparticles are uniformly grown on MOF / graphene oxide nanosheets, which can effectively solve the volume change problem during the polypyrrole doping-desodying process and greatly improve the cycle stability; Figure 3 The assembled supercapacitor device can successfully light up the LED signboard, showing good energy storage characteristics; Figure 4 The electrochemical performance of the MOF / graphene oxide / conductive polymer ternary composite material is shown. Figure 4 (a) is the CV curve of the material at different scanning rates. It can be found that with the increase of scanning rate, the shape of the CV curve remains almost unchanged, indicating that it has excellent rate characteristics. Figure 4 (b) shows the GCD curves at different current densities, and its specific capacitance is 707 F / g at a current density of 1 A / g. Figure 4 (c) The EIS curve shows that the material has extremely small internal resistance and excellent ion transport performance. Figure 4 (d) is the cycle stability curve of the material at a current density of 10 A / g. As shown in the figure, the capacitance retention rate is as high as 90% after 10,000 cycles.

[0034] Example 2

[0035] A method for preparing a MOF / graphene oxide / conductive polymer ternary composite material, which is different from Example 1 in that: 0.1 mmol (0.0189 g) of Zn(NO 3 ) 2 becomes 0.1mmol (0.0183g) of Ni(NO 3 ) 2; The mass of graphene oxide changed from 3.0 mg to 4.5 mg; the molar number of 2-methylimidazole changed from 0.8 mmol (0.0657 g) to 0.1 mmol (0.0082 g); the reaction time changed from 8 h to 12 h; the centrifugation at 5000 rpm for 20 min changed to the centrifugation at 6000 rpm for 15 min; the freeze drying for 12 h changed to the freeze drying for 18 h; the mass of the MOF / graphene oxide binary composite material changed from 20 mg to 24 mg; the phosphomolybdic acid of 0.06 mmol (0.1106 g) changed to 0.12mmol (0.3456g) of phosphotungstic acid; the stirring for 1h and ultrasonic dispersion for 30min in step (3) was changed to stirring for 1.2h and ultrasonic dispersion for 25min; 0.6mmol (40mg) of pyrrole monomer was changed to 0.4mmol (40mg) of aniline monomer; the stirring for 5min and ultrasonic dispersion for 30min in step (4) was changed to stirring for 10min and ultrasonic dispersion for 25min; the ammonium persulfate was changed from 0.6mmol (0.1369g) to 0.8mmol (0.1826g).

[0036] Example 3

[0037] A method for preparing a MOF / graphene oxide / conductive polymer ternary composite material, which is different from Example 1 in that: 0.1 mmol (0.0189 g) of Zn(NO 3 ) 2 becomes 0.1mmol (0.0183g) of Co(NO 3 ) 2 ; The mass of graphene oxide changed from 3.0 mg to 6.0 mg; dimethylimidazole changed from 0.8 mmol (0.0657 g) to 0.6 mmol (0.0493 g); the reaction time at room temperature changed from 8 h to 14 h; centrifugation at 5000 rpm for 20 min changed to centrifugation at 7000 rpm for 10 min; freeze drying for 12 h changed to freeze drying for 24 h; the mass of MOF / graphene oxide binary composite material changed from 20.0 mg to 28.0 mg; 0.06 mmol (0.1106 g) of phosphomolybdic acid changed to 0.24 mm ol (0.0470g) of ammonium molybdate; the stirring for 1h and ultrasonic dispersion for 30min in step (3) was changed to stirring for 1.4h and ultrasonic dispersion for 20min; 0.6mmol (40mg) of pyrrole monomer was changed to 0.28mmol (40mg) of 3,4-ethylenedioxythiophene monomer; the stirring for 5min and ultrasonic dispersion for 30min in step (4) was changed to stirring for 15min and ultrasonic dispersion for 20min; the ammonium persulfate was changed from 0.6mmol (0.1369g) to 0.28mmol (0.0639g).

[0038] Example 4

[0039] A method for preparing a MOF / graphene oxide / conductive polymer ternary composite material, which is different from Example 1 in that: 0.1 mmol (0.0189 g) of Zn(NO 3 ) 2 becomes 0.1mmol (0.0183g) of Ni(NO 3 ) 2 ; The mass of graphene oxide changes from 3.0 mg to 9.0 mg; the molar number of 2-methylimidazole changes from 0.8 mmol (0.0657 g) to 0.2 mmol (0.0164 g); the reaction time at room temperature changes from 8 h to 18 h; centrifugation at 5000 rpm for 20 min changes to centrifugation at 8000 rpm for 10 min; freeze-drying for 12 h changes to freeze-drying for 28 h; the mass of MOF / graphene oxide binary composite material changes from 20.0 mg to 32.0 mg; stirring for 1 h and ultrasonic dispersion for 30 min in step (3) changes to stirring for 1.6 h and ultrasonic dispersion for 15 min; stirring for 5 min and ultrasonic dispersion for 30 min in step (4) changes to stirring for 10 min and ultrasonic dispersion for 15 min; the molar number of ammonium persulfate changes from 0.6 mmol (0.1368 g) to 0.3 mmol (0.0685 g).

[0040] Example 5

[0041] A method for preparing a MOF / graphene oxide / conductive polymer ternary composite material, which is different from Example 1 in that: 0.1 mmol (0.0189 g) of Zn(NO 3 ) 2 becomes 0.1mmol (0.0183g) of Co(NO 3 ) 2 ; The mass of graphene oxide changes from 3.0 mg to 7.5 mg; the molar number of 2-methylimidazole changes from 0.8 mmol (0.0657 g) to 0.4 mmol (0.0328 g); the reaction time at room temperature changes from 8 h to 20 h; centrifugation at 5000 rpm for 20 min changes to centrifugation at 9000 rpm for 5 min; freeze drying for 12 h changes to freeze drying for 32 h; the mass of MOF / graphene oxide binary composite material changes from 20.0 mg to 36.0 mg; 0.06 mmol (0.1106 g) of phosphomolybdic acid changes to 0.36 mmol (0.6628 g) of silicomolybdic acid; stirring for 1 h and ultrasonic dispersion for 30 min in step (3) changes to stirring for 1.8 h and ultrasonic dispersion for 10 min; stirring for 5 min and ultrasonic dispersion for 30 min in step (4) changes to stirring for 20 min and ultrasonic dispersion for 10 min.

[0042] Example 6

[0043] A method for preparing a MOF / graphene oxide / conductive polymer ternary composite material, which is different from Example 1 in that: 0.1 mmol (0.0189 g) of Zn(NO 3 ) 2 becomes 0.1mmol (0.0183g) of Ni(NO 3 ) 2 ; The mass of graphene oxide changes from 3.0 mg to 12.0 mg; the molar number of 2-methylimidazole changes from 0.8 mmol (0.0657 g) to 1 mmol (0.0821 g); the reaction time at room temperature changes from 8 h to 24 h; centrifugation at 5000 rpm for 20 min changes to centrifugation at 10000 rpm for 5 min; freeze-drying for 12 h changes to freeze-drying for 36 h; the mass of MOF / graphene oxide binary composite material changes from 20.0 mg to 40.0 mg; stirring for 1 h and ultrasonic dispersion for 30 min in step (3) changes to stirring for 2 h and ultrasonic dispersion for 10 min; the molar number of ammonium persulfate changes from 0.6 mmol (0.1369 g) to 0.9 mmol (0.2054 g).

[0044] The electrochemical performance parameters of the ternary composite materials prepared in Examples 1-6 are shown in Table 1.

[0045] Table 1

[0046] Example 1 2 3 4 5 6 Ternary electrode specific capacitance value (F / g) 707 642 659 695 664 673 Energy density (Wh / kg) 55.2 52.4 52.3 54.1 52.8 53.1 10000 cycles stability (%) 90 92 90 92 91 93

[0047] The above embodiments describe the technical solutions of the present invention in detail. Obviously, the present invention is not limited to the described embodiments. Based on the embodiments of the present invention, people familiar with the technical field can also make various changes accordingly, but any changes that are equivalent or similar to the present invention belong to the scope of protection of the present invention.

Claims

1. A method for preparing a MOF / graphene oxide / conductive polymer ternary composite material, characterized in that: The steps include: (1) fully mixing the M(NO3)2 solution and the graphene oxide solution, then dropping a 2-methylimidazole solution into the mixed solution, and reacting at room temperature for 8-24 hours; (2) centrifuging, washing, and freeze-drying the solution obtained in step (1) to obtain a MOF / graphene oxide binary composite material; (3) dissolving the MOF / graphene oxide binary composite material obtained in step (2) in an aqueous solution of a dopant, stirring and ultrasonically dispersing to obtain a dispersion I for standby use; (4) injecting the conductive polymer monomer into the dispersion I obtained in step (3), stirring and ultrasonically dispersing to obtain a dispersion II for later use; (5) adding an aqueous ammonium persulfate solution dropwise to the dispersion II obtained in step (4) to react, and finally washing and drying to obtain a MOF / graphene oxide / conductive polymer ternary composite material.

2. The preparation method according to claim 1, characterized in that: The M(NO3)2 described in step (1) is one of Co(NO3)2, Ni(NO3)2, and Zn(NO3)2.

3. The preparation method according to claim 1, characterized in that: The molar concentration of the M(NO3)2 solution in step (1) is 2 mM, the molar concentration of the 2-methylimidazole solution is 2-20 mM, the concentration of the graphene oxide solution is 0.06-0.24 mg / mL, and the reaction time is 8-24 h.

4. The preparation method according to claim 1, characterized in that: The centrifugal speed described in step (2) is 5000-10000rpm, the centrifugal time is 5-20min, and the freeze-drying time is 12-36h.

5. The preparation method according to claim 1, characterized in that: The doping agent described in step (3) is one of phosphomolybdic acid, phosphotungstic acid, ammonium molybdate and silicomolybdic acid.

6. The preparation method according to claim 1, characterized in that: In step (3), the concentration of MOF / graphene oxide in the dispersion I is 1-2 mg / mL, the molar concentration of the dopant is 3-18 mM, the stirring time is 1-2 h, and the ultrasonic dispersion time is 10-30 min.

7. The preparation method according to claim 1, characterized in that: The conductive polymer monomer described in step (4) is one of aniline, pyrrole, and 3,4-ethylenedioxythiophene, and its concentration is 2 mg / mL. The stirring time is 5-20 minutes, and the ultrasonic dispersion time is 10-30 minutes.

8. The preparation method according to claim 1, characterized in that: The molar ratio of ammonium persulfate to conductive polymer monomer in step (5) is 2:1-1:2, and the reaction is carried out at room temperature for 12 hours.

Citation Information

Cited By

  • Ce, Nd-MOF-5 / GO / PANI composite material, preparation method and application thereof

    CN121215662A

  • Ce, Nd-MOF-5 / GO / PANI composite material, preparation method and application thereof

    CN121215662B

  • MOFs / GO / CC composite material, preparation method and application

    CN121583789A